A perspective on competitive freeride skiing and snowboarding - Mulder, Eric; Holmberg, Hans-Christer; Supej, Matej (Frontiers in Physiology, 2025)
Freeride skiing and snowboarding—collectively termed competitive freeriding—have evolved from niche extreme sports into formally recognized disciplines under the International Ski & Snowboard Federation (FIS). Unlike traditional alpine or freestyle events, competitive freeriding emphasizes creative line selection, technical execution, fluidity, style, and aerial maneuvers on natural, ungroomed mountain terrain. Athletes descend complex slopes based solely on visual inspection, without practice runs, facing unique physical and psychological challenges. This perspective article outlines the competition format and judging system, identifies key physiological and biomechanical demands, and reviews essential equipment and safety considerations. Despite growing popularity and institutional recognition, scientific research remains limited—primarily focused on avalanche risk and injury incidence—while other dimensions, such as psychological resilience, creative expression, and environmental connectedness, remain underexplored. Physiologically, competitive freeriders require high levels of eccentric and explosive strength, core stability, reactive control, and anaerobic endurance to navigate variable terrain and absorb impact during aerial maneuvers. Lower-extremity injuries—particularly anterior cruciate ligament (ACL) ruptures—are a major concern. Technological advances in drone-based filming, athlete monitoring, and protective equipment are reshaping freeride competition and broadcasting. As the sport moves toward potential Olympic inclusion, the central challenge lies in embracing innovation without compromising the core values of freedom, improvisation, and connection to the mountain environment.